Comparative study of joint range of motion in children between 7 and 12 years of age from different gender - S.I.L. Melo; V.J. Guth; A.C.S. Sousa; C. Sacomori; A.C.V. Martins; L. Lucca (Desafio Singular, 2011)
The aim of the study was to evaluate and compare active and passive joint range of motion in children in relation to gender and age. This study involved 103 children (43 boys and 60 girls) categorized into two groups: G1 (7 to 9 years old) and G2 (10 to 12 years old). The flexitest protocol, active and passive, and the SAPO® were used to evaluate joint range of motion. A paired t test was applied to compare active and passive joint range of motion and an independent t test (p < .05) was used to compare active and passive range of motion between gender and age. Results showed that the passive joint ranges of motion of the lower limbs are higher than active motion (p < .001). Girls presented greater passive ankle flexion than boys did (p = .002). Children between 7 and 12 years of age presented similar standards of joint range of motion of low limb. Significant differences were found between passive and active angular range of motion in the hip, knee and ankle. There were no differences between boys and girls in the joint range of motion as well as among age groups.